1981
DOI: 10.1128/iai.32.1.92-97.1981
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface mannan in the adherence of Candida albicans to fibrin-platelet clots formed in vitro

Abstract: An alkali-soluble extract from a cell wall preparation of Candida albicans was conjugated to sheep erythrocytes (SRBC) by using periodate oxidation or concanavalin A. Conjugated SRBC readily attached to a fibrin-platelet matrix, whereas nonconjugated SRBC did not. To determine the active component which promoted attachment of SRBC, the alkali-soluble fraction was treated with alpha-mannosidase, pronase, or glusulase or chemically degraded by acetolysis. The treated extract was then reconjugated with SRBC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Preliminary evidence suggests that this surface material consists largely of mannoprotein [7]. Recently, Maisch and Calderone [8] have proposed a role for cell-surface mannan in the adherence of C. albicans to fibrin-platelet matrices, while Sobel et al [5] have shown that pretreatment of C. albicans with trypsin or chymotrypsin significantly inhibits adherence of the yeast to vaginal epithelial cells. In the present study, two C. albicans isolates from symptomless carriers showed only a 2-fold increase in adherence to buccal epithelial cells even after growth in 500 mM galactose medium.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that this surface material consists largely of mannoprotein [7]. Recently, Maisch and Calderone [8] have proposed a role for cell-surface mannan in the adherence of C. albicans to fibrin-platelet matrices, while Sobel et al [5] have shown that pretreatment of C. albicans with trypsin or chymotrypsin significantly inhibits adherence of the yeast to vaginal epithelial cells. In the present study, two C. albicans isolates from symptomless carriers showed only a 2-fold increase in adherence to buccal epithelial cells even after growth in 500 mM galactose medium.…”
Section: Discussionmentioning
confidence: 99%
“…We used the mass of ␤-GPs noted in those experiments as the amount to be added to cell cultures. The supernatant for the alkali-soluble fraction was neutralized with glacial acetic acid and then concentrated by flash evaporation at 30°C, dialyzed against deionized water for 24 h, and lyophilized before use as the alkali-soluble fraction (64). Mannan from C. albicans was isolated as previously described by Kogan et al (65).…”
Section: Methodsmentioning
confidence: 99%
“…Work on the adherence of yeast led to the identification of cell wall components of C. albicans which may contribute to mucosal surface infection and penetration. Maisch & Calderone [ 100] suggested a role for surface mannan in the adherence of C. albicans to fibrin-platelet clots. Sandin et a/.…”
Section: Cell Surfacementioning
confidence: 99%